Ukuran Perusahaan, Kepemilikan Institusional, Struktur Kapital dan Nilai Perusahaan Publik di Indonesia - Ni Putu Mira Diantari Sadia (Universitas Pendidikan Nasional, 2019)
ABSTRACT The purpose of this study was to determine the importance of the role of corporate value in the manufacturing industry of public companies in Indonesia. Specifically, this study intends to examine whether company size and ownership structure play a role in increasing the value of the company, especially through the capital structure. This study focuses on manufacturing companies in Indonesia that are listed on the Indonesia Stock Exchange (IDX). Determination of company samples in this study was carried out by purposive sampling method, with the criteria of manufacturing companies listed on the Indonesia Stock Exchange during the period of 2016, the data collection method used in this study was the method of documentation study. The data analysis method used is Path Analysis. The results of the study, the minimum value of the company size was 12.74, while the maximum value was 30.87. The average value of company size is 23.98 with a standard deviation value of 4.87. Institutional ownership variables with a minimum value of 0.87 and a maximum value of 99.38 with an average value of 59.57 and a standard deviation of 29.22. The capital structure variable with a minimum value of 10.52 and the highest is 1658.82 with an average value of 133.98 and a standard standard deviation of 19.33. In the variable value of the company it is known that the minimum value is 0.14 and the highest is 62.78 with an average value of 3.35 and a standard deviation of 20.41. Noting the value of the cut-of-value and Goodness of fit results of the model, it appears that the criteria are good so that it is feasible to be used for further testing.